2016
DOI: 10.22146/jml.18786
|View full text |Cite
|
Sign up to set email alerts
|

EFEKTIVITAS KAPORIT PADA PROSES KLORINASI TERHADAP PENURUNAN BAKTERI Coliform DARI LIMBAH CAIR RUMAH SAKIT X SAMARINDA (The Effectiveness of Calcium Hypochlorite to Chlorination Process in Decreasing the Amount of Coliform Bacteria in the Wastewater of X)

Abstract: AbstrakKaporit pada limbah cair rumah sakit digunakan sebagai desinfektan, tetapi, penggunaan kaporit dengan dosis yang tidak tepat akan menyebabkan pembentukan senyawa Trihalomethane (THMs) yang beracun dan bersifat karsinogenik. Pada limbah cair rumah sakit X Samarinda, diperoleh nilai MPN Coliform sebesar >160.000 MPN / 100 mL dengan residu klor sebesar 0 ppm. Penelitian ini bertujuan untuk menentukan dosis optimum dari penggunaan kaporit menggunakan titik Breakpoint Chlorination (BPC) dan pengaruhnya terha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…Improper use of disinfectants can cause environmental damage. The study conducted by Busyairi et al (2016), showed that chlorination at a dose of 160 ppm with a contact time of 40 minutes caused the number of coliform bacteria to decrease by 98.83% (from 160,000 MPN/100 ml to 1866 MPN/100 ml) and it was found that there was a residual chlorine of 97.5 ppm.…”
Section: Aspects Of Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…Improper use of disinfectants can cause environmental damage. The study conducted by Busyairi et al (2016), showed that chlorination at a dose of 160 ppm with a contact time of 40 minutes caused the number of coliform bacteria to decrease by 98.83% (from 160,000 MPN/100 ml to 1866 MPN/100 ml) and it was found that there was a residual chlorine of 97.5 ppm.…”
Section: Aspects Of Technologymentioning
confidence: 99%
“…Giving chlorine to WWTP effluent does not necessarily reduce the number of pathogenic microbes, instead it has the potential to cause other microbes in the waters as effluent receiving water bodies to die due to residual chlorine (Prayitno et al, 2018). The study conducted by Busyairi et al (2016) application of 160 ppm chlorine with a contact time of 40 minutes resulted in a residual chlorine of 97.5 ppm. Escherichia coli bacteria in HWW proved to be resistant even though it had been chlorinated even at a concentration of 100 ppm.…”
Section: Social Aspectmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Tahun 2016 adalah tablet klorin 200 g dengan nilai MPN 1600 sel/100 ml (98,55%). Penggunaan klorin dalam bak klorinasi merupakan cara yang efektif untuk mengurangi kontaminasi Coliform karena khasiatnya sebagai desinfektan mampu merusak sel bakteri, merusak asam nukleat dan enzim (Busyairi et al, 2016).…”
Section: Suhuunclassified
“…Klorin menghasilkan senyawa organoklorin seperti Polychlorinated Bipheniyls (PCBs), dioksin, Dichloro Dietil Trichloromethana (DDT) dan lain-lain yang dapat mengganggu kekebalan, merusak hati dan ginjal, gangguan pencernaan, gangguan sistem saraf, gangguan sistem reproduksi bahkan kanker (Hasan, 2006). Oleh karena itu, penggunaan klorin yang efektif bertujuan untuk mengendalikan atau mengurangi residu klorin yaitu senyawa halogen organik dan trihalometana (THM) (Busyairi et al, 2016).…”
Section: Suhuunclassified